Microsoft Encarta world English dictionary 2001 (Microsoft, 2000)
This integrated source contains a dictionary, thesaurus, almanac, computer dictionary, style guide, and book of quotations, with over 60,000 audio pronunciations, 3000+ photos, illustrations, maps, and hundreds of audio clips (demonstrating musical styles, sound effects, etc.) contained in the dictionary.